HIV-1 Tat implicated as a key factor in viral spread. (July 2008) - Harrich, David; Apolloni, Ann; Warrilow, David
Evaluation of: Sahaf B, Atkuri K, Heydari K et  al. : Culturing of human peripheral blood cells reveals unsuspected lymphocyte responses relevant to HIV disease. Proc. Natl Acad. Sci. USA 105, 5111––5116 (2008). Following HIV-1 infection, Tat is amongst the first of the viral proteins to be expressed. Tat is a potent transcription activator protein rocketing HIV-1 gene expression in the infected cells, thus ensuring that high levels of all viral proteins, including Tat, are made. HIV-1-infected cells secrete Tat into the periphery where it causes pathogenic effects, such as stimulation of Kaposi''s sarcoma, immune modulation and cytotoxicity. Previous studies have demonstrated that T  lymphocytes can undergo apoptosis following exposure to exogenously added Tat. Here, Sahaf et al . caution that Tat had a dramatically different effect when it was added to cells cultured in incubators where the O2 tension was at physiological levels. Under these conditions, Tat actually stimulated T-lymphocyte proliferation and primed them for productive HIV-1 infection. Tat appears to have a new role during early HIV-1 disease by promoting viral spread. This curious and intriguing work has implications for our understanding of HIV-1 replication, and viral culture in general.